Current Status of Self‐Supported Catalysts for Robust and Efficient Water Splitting for Commercial Electrolyzer. Issue 24 (31st October 2019) - Kwon, Jiseok; Han, HyukSu; Choi, Seungun; Park, Keemin; Jo, Seonghan; Paik, Ungyu; Song, Taeseup
Abstract: The development of cost effective and high‐performance electrocatalyst is challenging but essential for realizing industrial hydrogen production by electolyzer. Electrocatalysts for water splitting must have active catalytic performance as well as high stability in strong alkaline or acidic media to be used in commercial elecrolyzer. Transition metal based electrocatalysts are considered as highly promising candidates due to their excellent oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) performance and stability with low materials cost. Recently, binder free self‐supported electrocatalysts based on transition metals have emerged as state‐of‐the‐art catalytic electrodes due to their high activity and robustness. These properties are attributed to lack of catalyst powder aggregation and a strong synergetic effect between the electrode surface and catalyst. In this mini review, recent development in self‐supported electrocatalysts for OER, HER and also bifunctional OER & HER are reviewed in terms of superior activity and robust stability. Material design strategies, structural and compositional properties, and catalytic performance of recently reported self‐supported electrocatalysts are summarized. Finally, overview of recent studies, challenges and prospects related to self‐supported electrocatalysts are discussed. Abstract : Self‐supported electrocatalyst : In this minireview, recent development of self‐supported electrocatalysts for OER, HER and also bifunctional (OER & HER) are reviewed in terms of superior activity and robust stability. Material design strategies, structural and compositional properties, and catalytic performance of recently reported self‐supported electrcatalysts are summarized. Finally, overview of recent researches, challenges and prospects on self‐supported electrocatalysts are discussed.